2019
DOI: 10.1002/adsu.201900029
|View full text |Cite
|
Sign up to set email alerts
|

Switch Effect, Water‐Like State, and New Interaction Mechanism of an H‐Bonded Polycation–Polyacrylamide System to Realize Instant Decolorization of Dyeing Wastewater

Abstract: technologies have been developed in the research literature, such as flocculation, adsorption, and oxidation decomposition. [12][13][14][15][16][17][18] Of these, flocculation is still more advantageous than the other technologies in the engineering applications of large-scale water treatment due to its simplicity, high efficiency, and cost-effectiveness. In engineering applications for dealing with dyeing wastewater, polycationic flocculants have been widely used as effective decolorization materials since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The results showed that the Cu (II) removal percentages for EPCG adsorption were increased with the increase of EPCG dosages from 0.20 to 0.30 g, indicating a saturated adsorption state at the EPCG dosages of 0.20–0.35 g. However, when the EPCG dosages were above 0.35 g, the Cu­(II) removal percentages for EPCG adsorption maintained an ultimate limit level and changed a little, indicating that the EPCG dosages were excessive. The maximal adsorption capacity ( Q max ) for EPCG adsorption was represented by the average values of the equilibrium adsorption capacities ( q e ) under the saturated adsorption states with the EPCG dosages being 0.20–0.35 g. The results showed that the maximal adsorption capacity ( Q max ) of EPCG adsorption was calculated to be 261.70 mg/g, which was higher than that of most of the selected existing adsorbents reported in the recent years , and was also lower than that of a few existing adsorbents , (Table ). However, the existing adsorbent materials are usually difficult to prepare due to the complex and expensive preparation process, or some of them are likely to cause another waste disposal problem after the water treatment process. In contrast, the EPCG preparation process was very facile, which was only through a facile cross-linking copolymerization and then a simple neutralization treatment.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The results showed that the Cu (II) removal percentages for EPCG adsorption were increased with the increase of EPCG dosages from 0.20 to 0.30 g, indicating a saturated adsorption state at the EPCG dosages of 0.20–0.35 g. However, when the EPCG dosages were above 0.35 g, the Cu­(II) removal percentages for EPCG adsorption maintained an ultimate limit level and changed a little, indicating that the EPCG dosages were excessive. The maximal adsorption capacity ( Q max ) for EPCG adsorption was represented by the average values of the equilibrium adsorption capacities ( q e ) under the saturated adsorption states with the EPCG dosages being 0.20–0.35 g. The results showed that the maximal adsorption capacity ( Q max ) of EPCG adsorption was calculated to be 261.70 mg/g, which was higher than that of most of the selected existing adsorbents reported in the recent years , and was also lower than that of a few existing adsorbents , (Table ). However, the existing adsorbent materials are usually difficult to prepare due to the complex and expensive preparation process, or some of them are likely to cause another waste disposal problem after the water treatment process. In contrast, the EPCG preparation process was very facile, which was only through a facile cross-linking copolymerization and then a simple neutralization treatment.…”
Section: Resultsmentioning
confidence: 89%
“…Our work assumption was derived from a series of fundamental researches developing new water purification materials for treating various types of wastewater (e.g., heavy-metal wastewater, dyeing wastewater, and papermaking wastewater) in our past contributions. In one of our previous contributions, we designed a novel polycarboxylate-based polyanionic gel (PAG) adsorbent material and discovered that it showed a higher adsorption capacity for Cu­(II) than the existing adsorbent materials. For the reasons, the polycarboxylate skeletons of PAG could form strong complex bonds with Cu­(II) so that the adsorption ability of PAG toward Cu­(II) could improve .…”
Section: Introductionmentioning
confidence: 99%
“…Dyeing wastewater has high toxicity, high chroma, and high chemical oxygen demands and is regarded as one of the main pollution sources for the global water environments. To purify the dyeing wastewater, it is key to remove the highly toxic and highly colored anionic dyes in the water. Absorption, flocculation, and oxidation decomposition have already been proved to be useful methods for purifying industrial wastewater. Of which, absorption is one of the most widely used and convenient methods for water treatment. The authors have observed that several traditional absorbent materials, for example, activated carbon absorbent, clay mineral (or solid waste) absorbent, and natural product absorbent, are usually used in the field of water treatment. , However, the absorption forces of these traditional absorbents are usually weak intermolecular forces, resulting in their relatively weak absorption abilities when being used for water treatment. , Thus, it is necessary to search for new absorbent materials for purifying dyeing wastewater.…”
Section: Introductionmentioning
confidence: 99%